Character Education Values in Introduction to Islamic Studies: A Transformative Scholarly Paradigm: Nilai-Nilai Pendidikan Karakter dalam Kajian Pengantar Studi Islam: Paradigma Keilmuan Transformatif - Moch. Farich Alfani; Muh. Syamsuddin; Rizki Isma Wulandari; Shaleh (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2024)
This study examines the values of character education contained in the Introduction to Islamic Studies. The values of character education are very important to facilitate students in an effort to form a noble, ethical, and berakhlaqul karimah personality. This research uses the SLR (Systematic Literature Review) method with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Data collection was carried out from the results of research that had been published in the period 2015–2023 in accredited national journals (Sinta 4, sinta 3, and Sinta 2) and internationally reputable journals. The results showed that there are several character education values in the study of Introduction to Islamic Studies, including: 1) Love to Allah SWT., the universe and its contents; 2) responsibility, discipline, and independence; 3) honest; 4) respect and courtesy; 5) compassion, care, and cooperation; 6) confident, creative, hard work, and never give up; 7) justice and leadership; 8) kindness and humility; and 9) tolerance, love of peace, and unity. Abstrak Penelitian ini mengkaji tentang nilai-nilai pendidikan karakter yang terdapat pada kajian Pengantar Studi Islam. Nilai-nilai pendidikan karakter sangat penting untuk memfasilitasi mahasiswa dalam upaya membentuk pribadi yang luhur, beretika, dan berakhlaqul karimah. Penelitian ini menggunakan metode SLR (Sistematik Literatur Review) dengan panduan PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analyses). Pengumpulan data dilakukan dari hasil penelitian yang telah dipublikasikan dalam kurun waktu tahun 2015 sampai dengan tahun 2023 pada jurnal nasional terakreditasi sinta 4, sinta 3, sinta 2 sampai dengan jurnal bereputasi internasional. Hasil penelitian menunjukkan bahwa terdapat beberapa nilai pendidikan karakter dalam kajian Pengantar Studi Islam, diantaranya; 1) Cinta kepada Allah SWT., semesta beserta isinya; 2) tanggung jawab, disiplin, dan mandiri; 3) Jujur; 4) Hormat dan santun; 5) Kasih Sayang, Peduli, dan Kerja sama; 6) Percaya Diri, Kreatif, Kerja Keras, dan Pantang Menyerah; 7) Keadilan dan Kepemimpinan; 8) Baik dan Rendah Hati; dan 9) Toleransi, Cinta Perdamaian, dan Persatuan.